2020
DOI: 10.5114/ada.2018.79225
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-Like Protein 2 in Psoriasis: a New Linkage with Metabolic Syndrome

Abstract: A b s t r a c tIntroduction: Psoriasis is a chronic disease of inflammatory nature which can be considered as a systemic disorder. Metabolic syndrome is prevalent in psoriatic patients, with a negative impact on disease severity. Angiopoietin-like protein 2 (ANGPTL2) role has been investigated in several chronic inflammatory conditions, but not in psoriasis. Aim: To evaluate the serum level of ANGPTL2 and its possible role in the occurrence of metabolic syndrome in psoriatic patients. Material and methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…This study validated several DEGs that are upregulated after MA, including angiopoietin-like 2 (Angptl2), which encodes a secreted pro-in ammatory glycoprotein 30 that maintains tissue homeostasis by regulating blood pressure angiogenesis and inducing in ammation 31,32 . A decrease in circulating ANGPTL2 levels leads to an increase in systolic blood pressure in humans and mice.…”
Section: Upregulated Degs In Shrs With Mamentioning
confidence: 67%
“…This study validated several DEGs that are upregulated after MA, including angiopoietin-like 2 (Angptl2), which encodes a secreted pro-in ammatory glycoprotein 30 that maintains tissue homeostasis by regulating blood pressure angiogenesis and inducing in ammation 31,32 . A decrease in circulating ANGPTL2 levels leads to an increase in systolic blood pressure in humans and mice.…”
Section: Upregulated Degs In Shrs With Mamentioning
confidence: 67%
“…An observational case–control study in Singapore identified common human leukocyte antigen alleles that put patients at risk for hyperlipidemia, hypertension, and psoriasis 28 . In a 2020 study, there was a higher prevalence of greater waist circumference, higher blood pressure, higher fasting blood glucose, and higher serum level of angiopoietin‐like protein 2 in study participants with psoriasis compared to those without psoriasis 29 . Patients with psoriasis also have an increased odds ratio for metabolic syndrome starting at ages 40–49 30 .…”
Section: Resultsmentioning
confidence: 99%
“…As regarding to Ang‐2, Kenawy and his team 12 illustrated that the serum level of ANG‐2 was high in psoriatic lesions as compared to healthy skin. Also, Wu et al 10 demonstrated the role of angiopoietin‐2 in inflammatory autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%